Pseudoaneurysm of the Pancreaticoduodenal Artery Associated with Duodenal Diverticulitis - Scarlett B. Hao; Dale B. Johnson; Hugo J. R. Bonatti (Case Reports in Surgery)
Background. Duodenal diverticula tend to be asymptomatic; however, patients may develop duodenal diverticulitis. Case Presentation. A 66-year-old Caucasian man presented to our emergency room with a two-day history of right-sided abdominal pain, chills, tachycardia, nausea, and emesis. His WBC, lactic acid, and bilirubin were elevated. CT-scan revealed an inflammatory process involving the gallbladder, the duodenum and ascending colon, a mesenteric soft tissue mass, and a diverticulum of the second portion of the duodenum. He was admitted, antibiotics were started, and he improved clinically over the next 36 hours. Repeat triple contrast CT-scan showed a two cm pseudoaneurysm (PA) of the pancreaticoduodenal artery causing a mesenteric hematoma. The inflammatory changes had significantly improved, and WBC and CRP were normalizing. Repeat CT-scan three days later demonstrated an interval increase in size of the PA. Angiography through celiac access and gastroduodenal artery demonstrated predominant inflow to the PA from the inferior pancreaticoduodenal artery. The superior mesenteric artery was accessed showing a replaced right hepatic artery hindering access to the branch feeding the PA. The patient was transferred to a specialized facility where ultimately occlusion of the PA inflow was obtained. The patient recovered without any complication from this rare condition. Conclusion. This seems to be the first reported case of duodenal diverticulitis causing a PA of the pancreaticoduodenal artery. Antibiotic therapy together with percutaneous embolization of the bleeding source resulted in a good outcome.